KNOWING THE FIGURE OF ISLAMIC WARRIORS JAMALUDDIN AL-AFGHANI - Ahmad Faqihuddin (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
Al-Afghani, as a reformer, views the importance of ijtihad; he also considers it essential to develop Salafiyah thought, a school that requires the teachings of Islam to remain pure as practiced by the early generations of Islam. Purely, Al-Afghani lived in Egypt for eight years. According to the Egyptian community, Al-Afghani simultaneously had no small influence on Muslims. According to the Egyptian intellectual M.S. Madkur Al-Afghanilah, who raised the intellectual movement in Egypt, this country achieved progress. Al-Afghani's Islamic thought is not just a discourse that becomes Islamic knowledge but becomes a movement. The progressive ones even became the inspiration for the Islamic revolutionary movements that emerged in the 20th century; this research is a literature study that concludes that Al-Afghani influenced the direction of the Islamic world figures such as Hassan Al Banna and his Muslim Brotherhood, Abul A'la al-Maududi. With the Jamaah Islam and arrival in Indonesia, Muhammad Natsir appeared with his Masyumi. Al-Afghani sebagai pembaharu memandang penting ijtihad, ia juga menganggap penting mengembangkan pemikiran Salafiyah, yaitu suatu aliran yang menghendaki ajaran Islam tetap murni sebagaimana yang diamalkan oleh generasi awal Islam, Al Afghani meyakini umat Islam akan bangkit dan akan mendapatkan kejayaan kembali setelah mengamalkan ajaran Islam secara murni,. Al-Afghani menetap di Mesir selama delapan tahun, menurut fihak masyarakat Mesir Al-Afghani mempunyai pengaruh yang tidak kecil bagi umat Islam di sama. Menuruat inteletual Mesir M.S. Madkur Al-Afghanilah yang membangkitkan gerakan intelektual di Mesir, sehingga negara ini mencapai kemajuan. Pemikiran Islam Al afghani bukan hanya sekedar wacana yang menjadi ilmu pengetahuan Islam, akan tetapi menjadi sebuah gerakan. Yang progresif bahkan menjdi inspirasi bagi gerakan-gerakan revolusi Islam yang muncul diabad 20, penelitian ini adalah penelitian kepustakaan yang menyimpulkan bahwa Al Afghani mempunyai pengaruh terhadap pergerakan dunia Islam tokoh-tokoh seperti Hassan Al Banna dengan ikhwanul musliminnya, Abul A’la al-Mududi dengan Jamaah Islamnya, dan sampai di Indonesia, muncul Muhammad Natsir dengan masyuminya.